1989
DOI: 10.1080/09553008914550981
|View full text |Cite
|
Sign up to set email alerts
|

Early Postirradiation Chromatin Degradation in Thymocytes

Abstract: The decrease in the average DNA size in thymocytes starts soon after in vivo irradiation and at approximately 45 min reaches a plateau, thereafter showing only minor changes up to 3 h. This fall in extent of chromatin cleavage coincides with the accumulation of 1.0-1.5 kb DNA fragments. Double-strand breaks generated by endonucleases are not randomly distributed along DNA but clustered in such a way that they give rise to fragments of 1-5 nucleosomes in size. Cycloheximide treatment partially inhibits nuclease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…after irradiation or injection). 4,5,28 The time-course of thymocyte DNA fragmentation by 5-Gy whole-body irradiation showed that the degradation was detectable as early as 3 hr after irradiation (Fig. 4b).…”
Section: In Vivo Degradation Of Thymocyte Dna During Thymic Atrophymentioning
confidence: 99%
See 2 more Smart Citations
“…after irradiation or injection). 4,5,28 The time-course of thymocyte DNA fragmentation by 5-Gy whole-body irradiation showed that the degradation was detectable as early as 3 hr after irradiation (Fig. 4b).…”
Section: In Vivo Degradation Of Thymocyte Dna During Thymic Atrophymentioning
confidence: 99%
“…21 Egg PC, at a ®nal concentration of 480 mM with 0Á1 mCi 1,2-di [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]palmitoyl PC, was dried under N 2 stream in the presence of 5 mM oleate and 1 mM PA. To this lipid mixture, an aqueous solution containing 10 mM CaCl 2 , 25 mM KF, 1Á5% (vol/vol) ethanol, and 50 mM HEPES, pH 7Á0, was added and sonicated in a bathtype sonicator for 1 min at room temperature. After addition of 20 ml of crude membrane suspension, the reaction mixture was incubated for 90 min at 308.…”
Section: Enzyme Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mitotic cell death, apoptosis is a relatively rapid and irreversible process which occurs within a few hours following IR exposure. Although documented in proliferating cell lines as well as tumor cells (Bump et al, 1994), IR-induced apoptosis was originally described in nonmitotic cells such as lymphocytes, which lead to the term of interphase cell death (Yamada and Ohyama, 1988;Soldatenkov et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, the presumed chain of events leads to Ca t + ion influx, activation of endonuclease, and DNA fragmentation as the immediate cause of cell death . Essentially the same features characterize radiation-induced apoptosis of thymocytes : DNA degradation (Soldatenkov et al 1989) and dependence on Cat + ions (Story et al 1992) . The apoptotic cells can be rescued by treatment with aurintricarboxylic acid (ATA), an inhibitor of endonuclease, although the specificity of ATA is doubtful (Eastman 1993) ; the sparing effect is reflected in both viability increase and decreased DNA fragmentation .…”
Section: Dna Damage and Degradationmentioning
confidence: 97%